The Relationship Between Body Weight and Recurrence of Bacteriologically Confirmed Pulmonary Tuberculosis Patients at Lampaseh Public Health Center in 2021–2024 - Nurul Fitria; Cut Putri Riska; Gisheila Julinda Tami; Rahmalia Hadiyana; Fina Faradina (Journal of Social Research, 2025)
Tuberculosis (TB) is an infectious disease caused by the Gram-positive bacterial infectious agent Mycobacterium tuberculosis which is an obligatory aerobic which generally attacks the lung organs in humans. This disease is transmitted by patients who spread through nuclei droplets that come out when the patient coughs or sneezes. Many new cases of tuberculosis are associated with malnutrition. The tendency to lose weight itself is a result of the symptoms of anorexia experienced by tuberculosis patients. Meanwhile, the inability to gain weight during therapy will be closely related to the risk of disease severity. The study aims to analyze the relationship between weight changes in patients with bacteriologically confirmed pulmonary tuberculosis and the recurrence of the disease at the Lampaseh Health Center from 2021 to 2024. This study uses a descriptive observational method with a cross sectional approach. The results show based on weight, the majority experienced weight gain, which amounted to 12 people (86%). Bacteriological confirmed pulmonary TB patients are equal in number between men and women, namely 7 people (50%) each. Age group of people with pulmonary TB. confirmed bacteriological highest in the age group of 40-59 years as many as 7 people (50%). Of all pulmonary TB patients who gained weight, none relapsed (0%). Meanwhile, those who lost weight or remained at a fixed weight and experienced a recurrence after undergoing treatment amounted to 1 person (50%). The conclusion of this study is that there is a relationship between the weight of patients with bacteriological confirmed pulmonary tuberculosis and the recurrence of pulmonary tuberculosis at the Lampaseh Health Center in 2021-2024.